Tendencias emergentes en el bienestar del cliente: un análisis bibliométrico (Tema Central) - Vargas González, Andrea (2025)
Over the years, a number of researchers have endeavoured to delve deeper into the concept of customer well-being. However, there is a scarcity of systematic research that organises and identifies the main currents and areas of study on this topic. In this line, a bibliometric research was carried out based on a critical analysis of the relevant studies that address the concept of customer well-being, leading to provide a comprehensive overview of the issues and approaches associated with this concept. To carry out this systematic literature review, a total of 410 articles published between 2000 and 2023 were collected and processed using VOSviewer software. The results show a significant increase in the number of publications, highlighting the existence of five clusters representing emerging research streams in the field of customer well-being. These clusters include transformative experience, customer satisfaction, subjective customer well-being, satisfaction psychology and motivational well-being. The fragmentation of the literature is discussed, focusing on variables such as motivation, emotions and experience. This analysis offers a comprehensive perspective on emerging trends in customer well-being, providing direction for future research in this field.